Covid-19 impact on food security and households poverty of red upland rice farmer in Semanu District, Gunungkidul Regency - Rahayu Lestari; Ayu Larasati Damas; Rozaki Zuhud; Wijaya Oki; Wisnu Rubiyanto Cahyo (BIO Web of Conferences)
COVID-19 shook the world and impacted the obstruction of production, distribution, buying, and selling activities, including food. Red upland rice is a primary food with a dryland cultivation system in Semanu District, Gunungkidul, the first area to cultivate red upland rice variety segreng. This study aims to determine the food security and poverty of red upland rice farmer households before and during COVID-19 and the factors that affect household food security. The research was conducted in Semanu District, and it was determined purposively. The sample size was 100 respondents by simple random sampling. Data were analyzed using quantitative analysis of income, expenditure, food security, poverty, and factors affecting household food security. The results showed that Covid-19 affected the decline in household income and expenditure. The food security of farmer households during COVID-19 experienced a decrease in the number of households in the food security category by 4%, while household poverty measured in rice equivalent showed a decrease in the number of non-poor households by 17%. Factors affecting the food security of red upland rice farming households in Semanu District are income, COVID-19, and gender.